The Social Impact Toward A North Carolina Man As Seen In Nicholas Sparks’ The Notebook - Siti Marda Yuliana (Fakultas Sastra Universitas Ekasakti, 2017)
The problem in this study is social impact from North Carolina citizen for the main character’s life. In the novel, Noah’s life is influenced by his social life, especially his love story with Allie. They are separated because of the difference of social class and people’s view about them who come from different status. From the result of this study found that, 1) social impact from people around to the main character in The Notebook novel, that is separating social class into three types, low class, middle class and high class, 2) social impact also influenced by the environment , which is North Carolina has beautiful view and make the people love their hometown by writing the poem, but in other side, environment makes space between people and their social status, 3) social impact is influenced by North Carolina citizen’s view who separate people based on the social class, and it makes the interaction between low class and high class is very limited, especially in relationship and marriage.